APPLYING FLIPPED LEARNING APPROACH IN EFL CLASSROOM IN LIEPAJA CENTRE PRIMARY SCHOOL - Bārdule, Kristīne (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Educational planning documents highlight the importance of differentiation of the learning process and improving individuals' competencies to fulfil complex tasks.  By a flipped learning approach, when the students acquire the new information at home, watching the instructional video, more time is devoted to the active learning process in the classroom, as a result of which the students have the opportunity to improve their competencies.Within this article's framework, a case study's data on using a flipped learning approach in teaching elementary school students are analysed. The study included fourteen 4th grade English as first foreign language students of Liepaja Centre primary school. The study was conducted in 2020 from 30 October till 27 November.The study's main objective is to analyse possibilities to differentiate the learning process according to students' individual needs and improve competencies using a flipped learning approach.The study found that teachers have an excellent opportunity to give students individual and useful feedback and differentiate students' work according to their individual needs. The study revealed that students have the possibility to improve competencies.It is useful to introduce teachers to the possibilities of a flipped learning approach to individualize the learning process and develop students' competencies as it is stated in education planning documents.